2019
DOI: 10.1038/s41598-019-52103-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and gut microbiome changes following GLP-1 or dual GLP-1/GLP-2 receptor agonist treatment in diet-induced obese mice

Abstract: Enteroendocrine L-cell derived peptide hormones, notably glucagon-like peptide-1 (GLP-1) and glucagon-like peptide-2 (GLP-2), have become important targets in the treatment of type 2 diabetes, obesity and intestinal diseases. As gut microbial imbalances and maladaptive host responses have been implicated in the pathology of obesity and diabetes, this study aimed to determine the effects of pharmacologically stimulated GLP-1 and GLP-2 receptor function on the gut microbiome composition in diet-induced obese (DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 81 publications
4
43
2
1
Order By: Relevance
“…Moreover, the results were inconsistent among those studies treated with liraglutide, sitagliptin, vildagliptin, and saxagliptin. In terms of β-diversity, there was higher cumulative evidence of significant difference after using metformin (5, 36-39, 41, 43-50, 54-56), and similar results were consistently reported among those studies treated with acarbose (5, 58-61), liraglutide (60,65,66,69,70), sitagliptin (5,60,73), and vildagliptin (6,74) across different mouse models. Evidence for the effects of other drugs was limited ( Table 9).…”
Section: Diversitysupporting
confidence: 67%
See 2 more Smart Citations
“…Moreover, the results were inconsistent among those studies treated with liraglutide, sitagliptin, vildagliptin, and saxagliptin. In terms of β-diversity, there was higher cumulative evidence of significant difference after using metformin (5, 36-39, 41, 43-50, 54-56), and similar results were consistently reported among those studies treated with acarbose (5, 58-61), liraglutide (60,65,66,69,70), sitagliptin (5,60,73), and vildagliptin (6,74) across different mouse models. Evidence for the effects of other drugs was limited ( Table 9).…”
Section: Diversitysupporting
confidence: 67%
“…The potential role of this mucin-degrading bacterium in ameliorating metabolic disorders was further confirmed by a series of animal experiments. For example, mice treated with metformin and liraglutide showed increased levels of A. municiphila in association with improved control of blood glucose and body weight (55,65). More importantly, HFD-fed mice treated with A. municiphila exhibited similar improvements in glucose tolerance and goblet cell production and inflammatory regulations as compared to the metformin treatment group (56).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, disruption of intestinal homeostasis and associated gut microbiome dysbiosis promote T2DM [28], and intensive insulin therapy and oral hypoglycemic agents recover gut microbiome dysbiosis [28][29][30]. In one study, the Firmicutes: Bacteroidetes ratio was reported to be elevated in HFD-fed mice and in obese humans [27]. Our results concur with these findings, although our HFD-fed Px rats were not obese.…”
Section: Discussionsupporting
confidence: 86%
“…Type 2 diabetes alters the gut microbiome, and host-gut microbiome interactions contribute to the efficacies of diabetic drugs [26,27]. In fact, disruption of intestinal homeostasis and associated gut microbiome dysbiosis promote T2DM [28], and intensive insulin therapy and oral hypoglycemic agents recover gut microbiome dysbiosis [28][29][30].…”
Section: Discussionmentioning
confidence: 99%